1997
DOI: 10.1017/s0033291797005709
|View full text |Cite
|
Sign up to set email alerts
|

Smooth pursuit eye movements in schizophrenia and affective disorder

Abstract: Low gain and high rates of intrusive saccades contribute to SPEM dysfunction in major depression. Abnormally high rates of catch-up saccades seem to be the oculomotor component in smooth pursuit, that is specific to schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…In studies of visual attention and perception, eye movements are used to investigate, e.g., how the focus of our attention is chosen depending on the content of an image [1], how objects are identified [2], and how decisions are made [3]. In medicine, eye tracking is employed in studies investigating the functionality of the brain, e.g., in patients with schizophrenia [4].…”
Section: Introductionmentioning
confidence: 99%
“…In studies of visual attention and perception, eye movements are used to investigate, e.g., how the focus of our attention is chosen depending on the content of an image [1], how objects are identified [2], and how decisions are made [3]. In medicine, eye tracking is employed in studies investigating the functionality of the brain, e.g., in patients with schizophrenia [4].…”
Section: Introductionmentioning
confidence: 99%
“…During periods of low gain smooth pursuit, “catch up” saccades are used to compensate for poor smooth pursuit gain (Flechtner et al, 1997; Friedman et al, 1991; Haarmeier, 1999; Levin et al, 1988). In contrast, during low gain vergence tracking we and others have observed few, if any, “catch up” vergence eye movements (Semmlow et al, 2007; Rambold et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Others argue that the incidence of intrusive anticipatory saccades is a more fundamental indicator of SPEM dysfunction in schizophrenia, reflecting a lack of inhibition in the system controlling saccades and eye fixations [19–21]. While these two viewpoints have been the major competing theories of SPEM dysfunction in schizophrenia, Flechtner et al recently raised doubts about these specific quantitative SPEM measures in general [22]. It was suggested that small saccades occurring near the target could be falsely defined as either catch‐up or anticipatory saccades, as the currently used eye movement recording systems do not provide an absolute index of eye position.…”
Section: Smooth Pursuit Eye Movement Dysfunction In Schizophreniamentioning
confidence: 99%